Some new aspects of land use in Slovenia - Gabrovec, Matej (Geografski zbornik, 1997)
Because of its exceptional role in determining the appearance of the landscape, land use has long been a recognized subject of research in geography as much abroad as in Slovenia. This article first gives a brief survey of the notable achievements of Slovene geographers. The continuation presents the results of analyses of the reciprocal correlation between land use and several important landscape elements (lithological structure, climate types, and altitude) carried out with the help of the Geographical Information System and the IDRISI computer program. Attention is drawn to new aspects of presenting the occurrence of individual land categories based on uniform large deviations from the average occurrence of certain categories in the country as a whole. Also presented are a test survey of predominant land use on the basis of arability equivalents and an improved survey of the typology of the change in land use, this time undertaken for the period between 1961 and 1994.
Keywords: agrarna geografija; družbena geografija; human geography; podeželje; raba tal; rural area; Slovenia; Slovenija; tipologija